Pelatihan Serbuk Instan Dan Teh Sachet Herbal Sebagai Upaya Promotif Dan Preventif Di Puskesmas Cendrawasih Kota Makassar - Sesilia Rante Pakadang; Sisilia Teresia Rosmaladewi; St Ratnah; Alfrida Monica Salasa (Jurusan Farmasi Politeknik Kesehatan Makassar, 2022)
Training Instant Powder And Herbal Sachets Tea As A Promotional And Preventive Effort In Cendrawasih Puskesmas City Of MakassarTraditional health services at the Public health center are training for conventional healers and herbal-based traditional medicine. The Traditional Health Independent Care Group is directly fostered by the pharmacist as the head of the pharmaceutical installation. This activity aims to increase participant's knowledge and provide training in making instant powders and herbal tea sachets. counseling on the function of herbs for promotive and preventive diseases and training on making instant powders for hypertension and tea sachets for tuberculosis. Participants in community service activities were 30 people, namely 20 cadres of traditional health self-care groups, and 10 perpetrators of herbal medicine carrying. There was an increase in participant knowledge of 42.86% as measured by a questionnaire. The success of the training is evidenced by direct practical activities from the participants after being given a training demo. Outputs: pack guidebook, guidebook intellectual property rights, instant powder products, and tea sachets in labeled packaging, 3 videos of packaging implementation online on YouTube, and packer articles. The results of the activity can be concluded that there is an increase in the knowledge and skills of the participants.Keywords: herbs, counseling, training, instant powder, tea sachets, herbsPelayanan kesehatan tradisional di puskesmas adalah pembinaan kepada pelaku pengobat konvensional dan pengobatan tradisional berbasis herbal. Kelompok Asuhan Mandiri Kesehatan Tradisional dibina langsung oleh apoteker sebagai kepala instalasi farmasi. Kegiatan ini bertujuan untuk meningkatkan pengetahuan peserta dan memberikan pelatihan pembuatan serbuk instan dan teh sachet herbal. penyuluhan tentang fungsi herbal untuk promotif dan preventif penyakit dan pelatihan pembuatan serbuk instan untuk hipertensi dan teh sachet untuk tuberkulosis. Peserta kegiatan pengmas 30 orang yaitu 20 kader kelompok asuhan mandiri kesehatan tradisional, 10 pelaku jamu gendong Terjadi peningkatan pengetahuan peserta sebesar 42,86% yang diukur dengan kuesioner. Keberhasilan pelatihan dibuktikan dengan kegiatan praktik langsung dari peserta setelah diberikan demo pelatihan. Luaran: buku panduan pengmas, HaKI (hak cipta) buku panduan, produk serbuk instan dan teh sachet dalam kemasan berlabel, 3 video pelaksanaan pengmas yang telah Online pada Youtube dan artikel pengmas. Hasil kegiatan dapat disimpulkan bahwa terjadi peningkatan pengetahuan dan keterampilan peserta.Kata kunci : herbal, penyuluhan, pelatihan, serbuk instan, teh sachet, herbal